Reaction of commercial cultivars of common bean to fusarium oxysporum f. sp. phaseoli (Research, Society and Development, 2020)
Common beans (Phaseolus vulgaris L.) are grown throughout the country and represent the main source of vegetable protein in the Brazilian diet. However, its production is strongly affected by biotic and abiotic factors, especially by diseases. Fusarium wilt, a disease caused by the fungus Fusarium oxysporum f. sp. phaseoli (Fop), is among the main diseases of this culture. The most efficient method for its control is the use of resistant cultivars, however, the lack of knowledge of the genetic and physiological variability of the pathogen hinders the development of resistant cultivars by breeding programs. In this sense, the objective of the present work was to characterize the reaction of the main commercial cultivars of common bean regarding resistance to different isolates of Fop. The bank of monosporic isolates was obtained from bean plants with symptoms of the disease in producing areas. The isolates were identified morphologically and molecularly by PCR. 14 commercial bean cultivars were inoculated with 5 distinct monosporic isolates and evaluated for wilt severity using the scale proposed by CIAT. In general, the commercial common bean cultivars evaluated showed resistance and intermediate resistance reactions to the studied Fop isolates, suggesting that possibly the PCR-SCAR marker was not efficient in the diagnosis of pathogen virulance and that the tested cultivars may have been unintentionally improved for Fusarium wilt resistance.